Evaluation of effective nucleon-nucleon potential and description of alpha-cluster type nuclei in restricted dynamics approach - Tambergs, J.; Ruza, J.; Krasta, T.; Alcaras, JAC; Katkevicius, O. (World Scientific Publ Co Pte Ltd, 1997)
The application of the Restricted Dynamics Approach in nuclear theory, based on the approximate solution of many-particle Schrodinger equation, which accounts for all conservation laws in many-nucleon system, is discussed. The Strictly Restricted Dynamics Model is used for the evaluation of binding energies, level schemes, E2 and M1 transition probabilities as well as the electric quadrupole and magnetic dipole momenta of light ct-cluster type nuclei in the region 4 less than or equal to A less than or equal to 40. The parameters of effective nucleon-nucleon interaction potential are evaluated from the ground state binding energies of doubly magic nuclei He-4, O-16 and Ca-40.